Characterization and spatiotemporal variations of ambient seismic noise in eastern Bangladesh - Bin Abdul Rahman, Syed Idros; Lythgoe, Karen; Muktadir, Md. Golam; Akhter, Syed Humayun; Hubbard, Judith (Frontiers in Earth Science, 2024)
This study analyses the ambient noise field recorded by the seismic network, TREMBLE, in Bangladesh, operational since late 2016. Horizontal-vertical spectral ratios confirm the placement of stations on sediment, many situated on thick sedimentary columns, consistent with Confidential manuscript submitted to Frontiers in Earth Science -Solid Earth Geophysics 2 local geology. Noise across the broadband spectrum is systematically examined. A high amplitude local microseism (0.4-0.8 Hz) is recorded, originating near the coast and modulated by local tides. The primary microseism (~0.07 -0.08 Hz) exhibits no seasonal changes in power but display strong horizontal energy which changes with seasons. The secondary microseism (0.15-0.35 Hz) correlates strongly with wave height in the Bay of Bengal and varies with seasons, with greater power and higher horizontal amplitude in the monsoon season when the wave height is highest. The microseism increases in amplitude and decreases in frequency as a tropical depression moves inland. Low frequency (0.02 -0.04 Hz) noise on the horizontal components has a 24-hour periodicity, due to instrument tilt caused by atmospheric pressure changes. A station located next to the major Karnaphuli River shows elevated energy at ~5 Hz correlated to periods of high rainfall. Anthropogenic noise (~4-14 Hz) is station-dependent, demonstrating changing patterns in human activity, such as during Ramadan, national holidays and the COVID pandemic. Our work holds implications for seismic deployments, earthquake, and imaging studies, while providing insights into the interaction between the atmosphere, ocean, and solid Earth.